Outlaw justice - Quintano, Gene, 1946-; Corcoran, Bill.; Kristofferson, Kris.; Jennings, Waylon; Nelson, Willie, 1933-; Tritt, Travis; Willett, Chad.; Banks, Jonathan, 1947-; Gracia, Sancho; Ribes, Federico; McClellan, Gordon; Gruska, Jay.; et al. (Santa Monica, Calif. : Artisan Home Entertainment, 2003)
Two aging gunfighters re-form their old gang to avenge the murder of one of their former members.
Special features: scene index, interactive menus.
Director of photography, Federico Ribes ; editor, Gordon McClellan ; music, Jay Gruska ; executive producer, Stanley M. Brooks.
Kris Kristofferson, Waylon Jennings, Willie Nelson, Travis Tritt, Chad Willett, Jonathan Banks, Sancho Gracia.
MPAA rating: R.
DVD, digitally mastered, 2.0 digital audio, Region 1 encoding, stereo.
Closed-captioned.
Keywords: Revenge -- Drama; Outlaws -- Drama; Feature films; Western films; Video recordings for the hearing impaired